La actividad acuática en el desarrollo psico-motriz en los niños y niñas con síndrome de Down de 7 a 10 años de la Unidad Educativa Especializada “Carlos Garbay” de la cuidad de Riobamba en el año lectivo 2015 – 2016. - Melena Cajamarca, Marisela Fernanda (2016)
The objective of this research was to analyze the water activities and psycho-motor development of children with Down syndrome from 7 to 10 years. In this research the two variables that were water activities and motor skills were evaluated. This theme was chosen to see that in the Special Education Unit "Carlos Garbay" a specific methodological guide for Down syndrome, much less evolutionary age of 7 to 10 years was not used; so one of the specific objectives was to create a methodological guide called "All to swim." The method used in this research was the Halliwick method, the method was field research and literature, the kind of research was analytical, descriptive and quasi-experimental research design is quanti and longitudinal type. We worked with a non-random population, also called probabilistic, and the entire population covered by 7 infants between children with Down syndrome 7 to 10 years of education Unit "Carlos Garbay". The technique used was the test, the instrument with which we worked was the test water activity and motor skills by the University of Rhode Island (USA), Taking the necessary parameters to assess water activities and psychomotor skills. Concluding that, after applying the post test of aquatic activity could be obtained the following results, which improved very positively, parameter adaptation water activity "enters the pool area" run unassisted 86%, while in the respiratory control in the activity parameter "Achieves complete immersion of the head" run unassisted by 71% in the prior to swimming in the activity Skills "floating in prone position parameter (head out) "run unassisted 14%, parameter swimming skills in the activity" turn and repositions "run unassisted 29%. The results obtained in implementing the post-test of motor skills show that within the parameter adaptation to the aquatic environment in the activity "sensory stimulation and reaction (accepts water) run unassisted 71% in the Autonomy parameter (self-help) activity "dressed after swimming" run unassisted 71%.